2022
DOI: 10.3389/fimmu.2022.963401
|View full text |Cite
|
Sign up to set email alerts
|

The significance of preclinical anti-BP180 autoantibodies

Abstract: Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering disease. Although the pathomechanism of BP onset has yet to be elucidated in detail, BP autoantibodies targeting two hemidesmosomal components, BP180 and BP230, are known to play a pivotal role in BP pathogenesis. Thus, the detection and measurement of BP autoantibodies are necessary for diagnosing BP and monitoring the disease activity. Immune assays such as immunofluorescence microscopy, immunoblotting, and ELISAs using BP180 and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 98 publications
2
11
1
Order By: Relevance
“…BP180 is usually elevated in bullous pemphigoid. The sensitivity and specificity of BP180 are 84.4% and 98.9%, respectively, in diagnosing bullous pemphigoid [ 8 ]. However, Sadik et al reported that the positivity of BP180 was observed in four out of nine bullous pemphigoid cases, which presented as skin irAE, from six German dermatology centers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…BP180 is usually elevated in bullous pemphigoid. The sensitivity and specificity of BP180 are 84.4% and 98.9%, respectively, in diagnosing bullous pemphigoid [ 8 ]. However, Sadik et al reported that the positivity of BP180 was observed in four out of nine bullous pemphigoid cases, which presented as skin irAE, from six German dermatology centers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several nonbullous dermatitis ircAE cases showed serum antibody positivity to the common blistering disease epidermal antigens, but these cases were not associated with the corresponding characteristic DIF findings. Of note, preclinical BP antibodies have been reported in aging patients with pruritus, neurological diseases, diabetes mellitus, and rheumatologic collagen diseases ( 58 ). Anti-DSG-1 and DSG-3 antibodies, along with other epidermal protein autoantibodies, have been found in paraneoplastic pemphigus and other autoimmune conditions ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have demonstrated the presence of anti-BP180 antibodies in healthy individuals. 5 The COVID-19 vaccination might exert an effector phase of BP (i.e., blister formation) in healthy individuals with anti-BP180 antibodies. Further, a prior COVID-19 vaccination may lead to autoantibody production, followed by development of BP later with or without repeated vaccinations.…”
Section: Ementioning
confidence: 99%